2011
DOI: 10.1002/pi.3054
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal effect of chitosan on the growth of Aspergillus parasiticus and production of aflatoxin B1

Abstract: Contamination of agricultural products by toxigenic fungi and the presence of mycotoxins cause serious economic damage, and toxic effects to humans and animals. In this study the effect of chitosan as a natural alternative for the control of the fungus Aspergillus parasiticus was evaluated. Chitosans were obtained from chitin previously extracted from shrimp heads using chemical (CS) and biological (CB) processes. The chitosan yields were 5.74 and 6.20% for CS and CB methods, respectively, with an amount of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…In addition, chitosan alone has the ability to inhibit aflatoxin production due to the Ca 2+ chelation. However, Cota-Arriola et al (2011) found that this inhibition did not occurred in corn grain, probably because the polymer is not able to penetrate into the grain, and thus limiting the ability for calcium chelation.…”
Section: Effect Of Microcapsules In Spore Germinationmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, chitosan alone has the ability to inhibit aflatoxin production due to the Ca 2+ chelation. However, Cota-Arriola et al (2011) found that this inhibition did not occurred in corn grain, probably because the polymer is not able to penetrate into the grain, and thus limiting the ability for calcium chelation.…”
Section: Effect Of Microcapsules In Spore Germinationmentioning
confidence: 98%
“…Four controls were prepared following the same procedure with no microparticles with EDs addedI: CS, water, and TPP with the inoculum and the fourth contained just 10 mL of water without inoculum. The extraction and quantification of fumonisin and aflatoxin was carried out according to Rosas-Burgos et al (2011) and Cota-Arriola et al (2011), respectively. Each treatment was replicated three times.…”
Section: Evaluation Of the Effect Of Microparticles With Eos In Mycotmentioning
confidence: 99%
“…Controls consisted of agar Czapek dox at pH 5.6 with and without FA at pH 5.6, CS 0.5% pH 5.6, and TPP 2% pH 5.6. The number of germinated spores, the percentage of spore germination inhibition, and the germination rate (spores h −1 ) were determined as described by Cota-Arriola et al (2011). Spore germination inhibition (FI) was calculated as follow:…”
Section: Spore Germinationmentioning
confidence: 99%
“…Spore germination is the first stage of fungal growth and is indicative of adaptation to the medium, because at this stage, the fungus produces the necessary compounds for its development (Cota-Arriola et al, 2011). It has been reported that calcium (Ca + ) and some enzymes, such as chitin synthase among others, play a fundamental role in the germination, mainly in the development of hyphae Table 2.…”
Section: Spore Germinationmentioning
confidence: 99%
“…Chitosan, the main deacetylated derivative of chitin, is a biocompatible, non-toxic, edible, biodegradable polymer, and it possesses antimicrobial activity against bacteria, yeast and fungi, including toxigenic fungi (Cota-Arriola et al, 2011). This polymer is the only natural cationic polysaccharide, which special characteristics makes it useful in numerous applications and areas, such medicine, cosmetics, food packing, food additives, water treatment, antifungal agent, among others (Hu et al, 2009).…”
Section: Chitosanmentioning
confidence: 99%